Umbilical Artery Doppler Indices Difference and Umbilical Cord Length: An Observational Study - Nesreen Fathy Ahmed Eisa; Moustafa Mahmoud Abdel Kawi; Mohamed Samir Sweed, Eman AbdElSalam NasrElDin (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The umbilical cord (UC) is responsible for transporting nutrients and oxygen through the fetal circulatory system. Abnormal UC length has been linked to adverse pregnancy outcomes. Doppler evaluation of the UA is a cheap, safe, and practical approach and does not require any special equipment. However, there is no defined method for measuring or predicting the length of the UC in the fetal period so far. This study investigates whether Doppler indices difference between placental and fetal ends of the UA is related to UC length or not. Patients and Methods: 120 singleton pregnant women at term candidate for elective cesarean section were recruited from the outpatient clinic of both Helwan University Hospital and Ain Shams University Maternity Hospital. Women who were recommended for study were examined by Doppler ultrasound on umbilical artery at fetal end, placental end and free loop for about seven minutes then Doppler indices were saved to be compared of the length of the umbilical cord after delivery, outcome complications, gestational age at delivery and (sex, weight, Apgar score) of the fetus. Results: In our study, there was significant negative correlation between umbilical cord length and umbilical artery S/D and RI at placental end. While there was no significant correlation between umbilical cord length and Doppler indices at fetal end and free loop. Also, there was statistically non-significant correlation between umbilical cord length and umbilical artery PSV, PI or EDV at placental end. There was statistically non-significant correlation between difference in PSV, EDV, PI, SD or RI and umbilical cord length. Our study showed 2 groups of umbilical cord length: group for the long cords and the other for the normal umbilical cords as no short chord was found in measurements. There was statistically significant difference of Doppler indices between two groups as regard PSV ratio at placental end which was significantly higher in patients with long umbilical cord and PI in fetal end which was higher in normal length cords.Conclusion: there is no significant correlation between difference in Doppler indices and umbilical cord length. PSV, EDV, S/D, PI and RI have highest value at fetal end which decrease at free loop and low level at placental end. PSV at placental end is higher in patients with long cords. There is high significant negative correlation between umbilical cord length and APGAR score.